The invisible sufferers of poverty: too many trees to notice the forest? International health policies to combat Neglected Tropical Diseases and poverty - Mancini, Elena (Medicina e Morale, 2022)
Diseases, especially infectious ones, have always accompanied the history of humankind, profoundly modifying economic structures and conditioning the social structures and cultural evolution of entire populations. All this is still true for a billion and a half people affected by diseases that the West has now forgotten and that are endemic in tropical areas of the planet (Neglected Tropical Diseases). Enormously facilitated by poverty, they are, in turn, one of the main causes of poverty and one of the most insidious obstacles to the development of vast geographical areas of Asia, Africa and Latin America. It is necessary to fight poverty in order to reduce disease, but it is also necessary to eliminate disease in order to lift people out of poverty and foster development. However, fighting NTDs means dealing with contexts marked not only by poverty, but also by precarious social balances, dramatic hygienic-sanitary conditions, absence or inadequacy of infrastructures and health systems, various forms of discrimination and social exclusion of patients: all factors that hinder any action starting from the very collection and verification of epidemiological data. This paper examines some intervention strategies inspired by the community-driven approach, aimed at involving local communities in the integration and management of prevention measures. The role of informal health workers (Community Health Workers) in the dissemination of behaviors, information and prophylaxis tools, and in the enhancement of marginal local practices that have nevertheless proven effective in combating or preventing one or more NTDs (positive deviance) is also studied. A final consideration is dedicated to the training of CHWs for the purpose of community health education.